Student challenges in academic paragraph writing: A study in Aceh, Indonesia - Hermida, Rita (Accentia: Journal of English Language and Education, 2024)
This study investigates the common writing challenges faced by students when composing academic paragraphs. Focusing on key areas including content development, vocabulary usage, language fluency, mechanical accuracy (grammar, punctuation), and organizational structure, the study aims to identify specific writing difficulties. A quantitative approach was employed, utilizing questionnaires to gather data from 35 students at English Education department in Aceh, Indonesia. Key findings revealed that content development posed the most significant challenge, reported by 65% of participants. Vocabulary usage followed closely at 60%, while language fluency presented difficulties for 50% of students. Mechanical accuracy and organizational structure each presented challenges for 45% of participants. These findings underscore the critical need for targeted support to address specific areas of writing difficulty, particularly in content development and vocabulary usage, to enhance students' academic writing proficiency.